Working and Learning with First Peoples of Australia in the Creative Arts : a Framework to Support Respectful and Mutually Beneficial Service Learning Partnerships in the Creative Arts. - Bartleet, Brydie-Leigh; Bennett, Dawn; Power, Anne; Marsh, Kathy; Sunderland, Naomi (Office for Learning and Teaching, 2014)
Resource document produced during a project that aimed to demonstrate how collaborative partnerships between students and Indigenous communities can create Indigenous curriculum content in culturally appropriate ways. Using service learning as its pedagogical framework and performing arts as its disciplinary base, the project extended prior work in this field to communicate how these projects develop students' intercultural competencies, transform their understandings of Indigenous culture, and support Indigenous communities through cultural knowledge exchange. This document is a framework to support respectful and mutually beneficial service learning partnerships in the creative arts.